Role of inositol phospholipid signaling in natural killer cell biology - Gumbleton, Matthew; Kerr, William G. (Frontiers in Immunology, 2013)
Natural Killer (NK) cells are important in the host defense against malignancy and infection. At a cellular level NK cells are activated when signals from activating receptors exceed signaling from inhibitory receptors. At a molecular level NK cells undergo an education process to prevent autoimmunity. Mouse models have shown important roles for inositol phospholipid signaling in lymphocytes. NK cells from mice with deletion in different members of the PI3K signaling pathway have defective development, natural killer cell repertoire expression (NKRR) and effector function. Here we review the role of inositol phospholipid signaling in NK cell biology.